Do Social Network Sites Enhance or Undermine Subjective Well‐Being? A Critical Review. Issue 1 (January 2017) - Verduyn, Philippe; Ybarra, Oscar; Résibois, Maxime; Jonides, John; Kross, Ethan
Abstract : Social network sites are ubiquitous and now constitute a common tool people use to interact with one another in daily life. Here we review the consequences of interacting with social network sites for subjective well‐being—that is, how people feel moment‐to‐moment and how satisfied they are with their lives. We begin by clarifying the constructs that we focus on in this review: social network sites and subjective well‐being. Next, we review the literature that explains how these constructs are related. This research reveals: (a) negative relationships between passively using social network sites and subjective well‐being, and (b) positive relationships between actively using social network sites and subjective well‐being, with the former relationship being more robust than the latter. Specifically, passively using social network sites provokes social comparisons and envy, which have negative downstream consequences for subjective well‐being. In contrast, when active usage of social network sites predicts subjective well‐being, it seems to do so by creating social capital and stimulating feelings of social connectedness. We conclude by discussing the policy implications of this work.